2016
DOI: 10.1007/s00380-016-0868-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the augmentation index derived vascular age in patients with newly diagnosed atherosclerosis

Abstract: Early detection of atherosclerosis, i.e., in occupational health screening programs could reduce the rate of cardiovascular events in the working population. Changes of the augmentation index (AIX) correlate with changes of the arterial stiffness induced by aging, atherosclerosis, or arterial hypertension and have a prognostic value for cardiovascular events. Their diagnostic yield should be increased by normalizing the AIX to age, in terms of a calculating the vascular age (VA). In this pilot study, 30 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Based on the Anglo-Cardiff Collaborative Trial, which examined the pattern of AIx of 4001 individuals from the general population, AIx showed prominent changes in those aged under 50 years, whereas aortic PWV showed prominent changes with age in those over 50 years 46. AIx is elevated in patients with atherosclerosis compared with health controls while aortic PWV remained within normal ranges and did not differ between the groups 47. Aortic wave reflections may offer an early indicator of atherosclerosis compared with PWV which may have prognostic value for CV events in patients with atherosclerosis.…”
Section: Arterial Stiffness and Wave Reflectionsmentioning
confidence: 76%
“…Based on the Anglo-Cardiff Collaborative Trial, which examined the pattern of AIx of 4001 individuals from the general population, AIx showed prominent changes in those aged under 50 years, whereas aortic PWV showed prominent changes with age in those over 50 years 46. AIx is elevated in patients with atherosclerosis compared with health controls while aortic PWV remained within normal ranges and did not differ between the groups 47. Aortic wave reflections may offer an early indicator of atherosclerosis compared with PWV which may have prognostic value for CV events in patients with atherosclerosis.…”
Section: Arterial Stiffness and Wave Reflectionsmentioning
confidence: 76%
“…In this study, the feasibility of predicting ABI from multisite PPG features employing a linear machine learning procedure (i.e., GLM) was investigated. ABI was measured using a commercially available instrument (Enverdis Vascular Explorer, VE) [31,32], which is able to measure the ankle and brachial pressures. GLM was then employed in a supervised learning approach [27] to link different features extracted from the PPG signals at the ankle and at the arm with ABI estimated using the Vascular Explorer (VE-ABI).…”
Section: Introductionmentioning
confidence: 99%
“…Although arteriosclerotic disease typified by acute coronary syndrome (ACS) is the main cause of death, it has been reported that the onset age of ACS has also growing order [ 1 ]. Moreover, the relationship between vascular age and arteriosclerotic diseases has also been reported [ 2 ]. Therefore, the prevention and treatment of these arteriosclerotic diseases are important.…”
Section: Introductionmentioning
confidence: 99%